2023
DOI: 10.1002/adma.202209692
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Sonodynamic Cancer Therapy Performance of 2D Layered Double Hydroxide Nanosheet‐Based Sonosensitizers Via Crystalline‐to‐Amorphous Phase Transformation

Abstract: Figure 1. Schematic illustration of the preparation of a-CoW-LDH-PEG nanosheets and their application in SDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 60 publications
(80 reference statements)
0
54
0
Order By: Relevance
“…By contrast, SDT and CDT that does not need light activation are comparatively promising for treating bone tumors and worthy of further study. For example, Hu et al [280] realized the phase transition of CoW-LDH and NiW-LDH nanosheets from polycrystalline to amorphous by simple acid etching treatment, as a high-efficiency sonosensitizer for SDT. Due to the defect generation induced by phase transformation and electronic structure changes, amorphous CoW-LDH nanosheets appear to have higher ROS-generating ability under ultrasound irradiation and achieve effective tumor-killing effects.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…By contrast, SDT and CDT that does not need light activation are comparatively promising for treating bone tumors and worthy of further study. For example, Hu et al [280] realized the phase transition of CoW-LDH and NiW-LDH nanosheets from polycrystalline to amorphous by simple acid etching treatment, as a high-efficiency sonosensitizer for SDT. Due to the defect generation induced by phase transformation and electronic structure changes, amorphous CoW-LDH nanosheets appear to have higher ROS-generating ability under ultrasound irradiation and achieve effective tumor-killing effects.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…However, there has been a report on CoW-LDH, which can function as high-efficiency inorganic sonosensitizers for sonodynamic cancer therapy in recent years. [104] As shown in Figure 16A(a), the a-CoW-LDH nanosheets were prepared via CoW-LDH under US irradiation. Its SDT performance is ≈5 times better than LDHs, which is attributed to the crystalline-to-amorphous phase transformation-induced bandgap narrowing, electronic structure changing, and defect generation.…”
Section: Sonodynamic Therapymentioning
confidence: 99%
“…Reproduced with permission. [104] Copyright 2023, Wiley-VCH. B(a)) Illustration image of exfoliation of bulk MoS 2 .…”
Section: Sonodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Liang group dispersed the as-prepared CoW-2D layered double hydroxide (CoW-LDH) nanosheets in phosphate buffer solution (pH = 4) for different times (0.5, 2, 4, 6, 12, 24 h) to obtain amorphous CoW-LDH (a-CoW-LDH). [67] They found that acid etching produced abundant oxygen vacancy defects on CoW-LDH nanosheets and caused W 6+ to be partially reduced to W 5+ . These structural changes lead to the phase transition of CoW-LDH nanocrystals from crystal to an amorphous phase.…”
Section: Introduction Of Defects Into Presynthesized Nanomaterialsmentioning
confidence: 99%